Adapted work placement delivery method under COVID-19 towards students' job preparatory behaviours. Issue 6 (December 2022) - Dewi, Rahmatika
This study investigated students' perceptions of an adapted work placement (WP) delivery method due to COVID-19, their intention of finding paid jobs or becoming self-employed and how the intention influenced their job preparatory behaviours (JPB). Ajzen's Theory of Planned Behaviour (TPB) was utilised as a theoretical framework to model the research design. The TPB framework has three constructs – attitude towards behaviour, subjective norm and perceived behavioural control – that lead to students' intentions with regard to future jobs and, ultimately, behaviours. The study analysed three sets of data from: (i) semi-structured interviews with accounting students, (ii) a semi-structured interview with the head of an accounting department, (iii) document analysis of a WP guidebook. All data were collected from a polytechnic in Indonesia. There were three key findings. In terms of students' perceptions, the adapted WP programme created disappointment among the students. Beyond this disappointment, the adapted delivery method unexpectedly increased the students' self-employment intentions. Nonetheless, the intentions did not entirely prompt the students to pursue JPB towards self-employment. This paper provides insights into how higher education institutions might restructure their WP programmes, especially in times of crisis, and provides suggestions for students' job preparations.